Eugenol-Rich Essential Oil from Pimenta dioica: In Vitro and In Vivo Potentialities against Leishmania amazonensis - Lianet Monzote; Laura Machín; Adiel González; Ramón Scull; Yamilet I. Gutiérrez; Prabodh Satyal; Lars Gille; William N. Setzer (MDPI AG, 2023)
Pimenta dioica L. is one the most recognized species with diverse biological activities. In this study, in vitro activity and in vivo efficacy of essential oil from P. dioica (EO-Pd) was evaluated. The main compound was also included in the animal studies and its in silico prediction related to biological activities, molecular ligands, drug likeness, and ADME (absorption, distribution, metabolism, and excretion) properties are listed. The chemical composition analyzed by GC-MS retrieved 45 components, which the most abundant compound was the eugenol (80.1%). The EO-Pd was able to inhibit the growth of L. amazonensis (IC50 = 9.7 ± 0.7 and 11.3 ± 2.1 µg/mL, promastigotes and amastigotes, respectively). The cytotoxicity assay showed a CC50 of 104.5 ± 0.9 µg/mL and a selectivity index of 9. In the model of cutaneous leishmaniasis in BALB/c mice, the effect of EO-Pd and eugenol was observed after treatment at 30 mg/kg by intralesional route with 5 administrations every 4 days. In the in silico predictions, some targets that justified the antileishmanial activity of eugenol and good drug like properties for this compound, were obtained. This study showed for first time the potential of EO-Pd to inhibit L. amazonensis, which could be linked to the activity of major compound eugenol.